(3eMGSHI GdeGdjI GdeYebI (B1 : s (3eMGSHI h eGdjI , eMGSHI h eQGLYI , eMGSHI h LHGjI , eGdjI GdeDSSI (B: (3GdSfI (B3 (3GdSOGSj (B5 / s - (3WHjHd, YHO GdSdGes; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3GdJSHjbGJ , GdJNajVGJ h GdahGJjQ , eMGSHI GdCZdaI GdeJbOeI h eMGSHI GdGhQGb GdLGQjI , eMGSHI GdGLhQ , GdYbhO Ydi GdeOi GdWhjd s
(3eQGLY U(B.168s
Keywords: (3GdeGdjIs; (3GdeMGSHIs; (3GdeMGSHI GdeGdjIs